Spinning Top Urethra and Lower Urinary Tract Dysfunction in a Young Female - P.N. Dogra; M.S. Ansari (The Scientific World Journal)
Spinning top urethra (STU) denotes a particular urethral configuration that is a dilated posterior urethra mainly seen in young girls or women. STU deformity arises secondary to detrusor instability, leading to a rise the intravesical pressure against a closed sphincter. We describe a case of spinning top urethra in a 30-year-old woman who presented with lower urinary tract symptoms and left flank pain.